Prediction of Air Quality Based on Hybrid Grey Double Exponential Smoothing Model - Zhicun Xu; Meng Dun; Lifeng Wu (Complexity)
To predict the concentration of air pollutants accurately, conformable fractional accumulation grey double exponential smoothing and adjacent accumulation grey double exponential smoothing are proposed, respectively. A hybrid model with conformable fractional accumulation and adjacent accumulation is proposed to further improve the prediction accuracy. The hybrid model is applied to the prediction of AQI, PM2.5, and PM10. Compared with the traditional double exponential smoothing model, the new model has a higher prediction accuracy.